ESTIMATION OF BAD WEATHER CONDITIONS INFLUENCE ON DIFFERENT PHASES OF FLIGHT USING EXPERT JUDGEMENT METHOD - Shmelova, Tetiana; Maksymchuk, Zhanna (Proceedings of National Aviation University (archive), 2019)
Purpose: estimation of the influence of five different types of bad weather conditions: fog, wind shear, thunderstorm, icing and snow on the aircraft operations during three stages of flight: takeoff and climb, enroute, descent and landing. Methods: using the significance of influence on the flight operations as the parameter of comparison, bad weather conditions are compared by experts in their questionnaires. With the help of expert judgement method, the experts’ group opinions are obtained, coordinated, the significance of calculations criteria and weight coefficients are calculated. Using the results of calculations, the general histogram of weight coefficients for three different stages of flight is built, representing the significance of bad weather conditions influence on aircraft operations. Results: the expert system methodology presented in this work helps to evaluate the impact of weather events on the flight operations and select the appropriate measures of preventing bad weather conditions influence on each stage of flight. Discussion: the derived expert system can be used in airplane operations to evaluate the impact caused by weather, for further improvement of the situational awareness and decision making process of aviation staff with the application of new artificial intelligence technologies.